Jews on Broadway an historical survey of performers, playwrights, composers, lyricists and producers - Lane, Stewart F. (McFarland & Co., 2011)
"Jewish performers, composers, lyricists, directors, choreographers and producers have made an indelible mark on Broadway for more than a century. This historical volume captures the story of the Jewish emergence from immigrants in ghetto living conditions staging Yiddish Theater productions on New York's Lower East Side to their significant social and cultural impact on the stages of Broadway" --Provided by publisher.